Greener pastures for the livestock industry - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
seminar on Livestock development policies in the humid and sub-humid zones of sub-Saharan Africa. The seminar was held in Abidjan, Cote d'lvoire, 5-9 February 1996